PM.06 Low Molecular Heparin Within the Uteroplacental Unit. (26th April 2013) - Ismail, SK; Norris, L; Kelly, L; Higgins, JR
Abstract : Background: Perturbation of the uteroplacental haemostasis has been implicated in placenta mediated pregnancy complications in thrombophilic women. LMWH may be effective in altering local thrombin production in the uteroplacental compartment. Aim: We determined the effects of LMWH (tinzaparin) on the peripheral, uteroplacental and fetal circulation and on haemostatic gene and antigen expression in placental tissue. Method: Eight women on antenatal LMWH prophylaxis (tinzaparin 75 IU/kg) due to moderate risk of VTE undergoing caesarean section (CS) and a control group of 15 healthy pregnant women undergoing CS had venous blood taken from the peripheral and uterine vein before delivery of placenta. Simultaneously, cord venous blood and placental biopsy was collected. Tissue factor pathway inhibitor (TFPI), thrombin antithrombin (TAT) and endogenous thrombin potential (ETP) were measured. Real-time PCR and ELISA were used to quantify mRNA and protein expression of TFPI and TF in placental tissue. Results: TAT levels within uterine vein are significantly higher compared to maternal peripheral circulation in both the control group (P < 0.0001) and LMWH group (P < 0.02). In the LMWH group, TAT is reduced compared with controls in the uterine vein (P < 0.001). ETP and TFPI within uterine circulation is reduced significantly in the LMWH group (P < 0.05) and (P < 0.02) respectively. Down-regulation of placental TFPI and TFPI2 mRNA expression was also found (p < 0.05). Placental TF mRNA expression in LMWH group showed a non significant increase compared to control and this is replicated in placental TF antigen expression. Conclusion: TAT is reduced in uteroplacental circulation in thrombophilic women on LMWH prophylaxis and this is mirrored by decreased ETP in uteroplacental circulation. LMWH may be effective in reducing in- vivo thrombin production in the uteroplacental circulation of thrombophilic women.